An ANALYSIS OF GRAMMATICAL ERRORS IN WRITING NARRATIVE TEXT B: AN ANALYSIS OF GRAMMATICAL ERRORS IN WRITING NARRATIVE TEXT BY STUDENTS GRADE EIGHT AT SMP SWASTA VALENTINE DELI SERDANG - Rinda Nababan; Yosiardi Tarigan; Elma Gibra Br Ginting; Natalia Widya Pasca Tarigan (elt, 2021)
Abstract The researchers conducted this research to find out some of the mistakes made by students in writing, especially in writing narrative text. The researchers involved several grade VIII students of SMP SWASTA VALENTINE DELI SERDANG in academic year 2020/2021. The researchers conducted a qualitative descriptive study with 15 students participating in the study by giving them a questionnaire test. This study found 4 types of grammatical errors in students' writing, namely spelling, verb tense, article, and capitalization with the following number of errors. 1: Spelling with 29 errors = 18.70%, Verb tense with 69 errors = 44.51%, Articles with 31 errors = 20% and Capitalization with 26 errors = 16.77% . The total accumulated grammar mistakes made by the students were 155. Keywords: analysis, grammatical errors, narrative text.